The Role of CIPSI in Epistemic Decolonization: Integrating Islamic Philosophy and Local Wisdom into Educational Reform in Indonesia - Al Akbar, Nuruddin (Islamic Studies Review, 2025)
This paper explores the role of the Center for Islamic Philosophical Studies and Information (CIPSI) in decolonizing education in Indonesia, focusing on its efforts to challenge colonial influences by integrating Islamic philosophy and local educational systems into the curriculum. CIPSI contributes to a culturally relevant educational model by translating key Islamic texts, conducting research in Islamic philosophy, science, and mysticism, and advocating for the inclusion of local wisdom. This study highlights CIPSI’s role in bridging Islamic and Western knowledge systems, emphasizing the importance of indigenizing curricula. The paper also examines the challenges CIPSI faces and how non-state actors can collaborate with state institutions to reform the education system, contributing to the development of an educational framework that reflects Indonesia’s cultural and intellectual heritage.